Incidence of Ovarian Cysts in Patients Taking Ovulation Induction with Clomiphene Citrate (Medical Forum Monthly, 2021)
Objective: To determine the frequency of ovarian cyst in patients of induced ovulation.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology, Shahida Islam Teaching Hospital Lodhran from September 2019 to August 2020.Materials and Methods: A total of 214 patients with infertility planned for ovulation induction, 20-35 years of age were included. Patients with preexisting ovarian cyst were excluded. To all patients clomiphene citrate 50 mg was given from day 2 to day 6 of menstrual cycle. Serum progesterone levels were done on day 21 of cycle. If progesterone levels were > 30ng/dl then same dose of clomiphene citrate was given in next cycle. If day 21 progesterone levels were < 30 ng/dl then 100 mg of clomiphene citrate was given in 2nd cycle. In this cycle serum progesterone levels were done on day 21 and day 24. If progesterone levels were < 30 ng/dl then increments in the dose was made to a maximum dose of 150 mg per day in 3rd cycle. As part of protocol, in every patient trans-vaginal ultrasound was repeated before prescribing clomiphene citrate.Follicular tracking was added for monitoring of ovulation. After 3rd cycle pelvic ultrasound was done to diagnose any ovarian cyst.Results: Age range in this study was from 20 to 35 years with mean age of 29.27 ± 2.34 years. Majority of the patients 132 (61.68%) were between 20 to 30 years of age. Mean duration of infertility was 3.81 ± 1.63 years. Mean BMI was 28.53 ± 2.59 kg/m2. Mean dose of clomiphene citrate was 84.63 ± 21.63 mg. Frequency of ovarian cyst in patients of induced ovulation was found in 22 (10.28%) patients.Conclusion: This study concluded that frequency of ovarian cyst in patients of induced ovulation is quite high.